Influence of Resistance Spot Welding Parameters on Cold-Formed Steel Properties and Failure Modes - Hulka, Iosif; Ungureanu, Viorel; Both, Ioan; Petzek, Edward; Radu, Bogdan (Salehan Institute of Higher Education, 2025)
Lightweight steel structural systems such as built-up beams and trusses are efficient and easy to handle, but the joining technique between thin-walled cold-formed steel elements requires improved solutions. Conventional welding technologies are not suitable for connecting thin sheets due to several inconveniences. The study presents a novel technological approach to connect lightweight steel beams made of corrugated galvanised sheets for webs and back-to-back lipped channel profiles for flanges connected by spot welding, as resistance spot welding (RSW) is widely used in various industrial sectors, such as automotive. This study investigates the influence of RSW parameters on the microstructural properties of spot-welded low-carbon galvanised steel sheets, as well as on their mechanical properties. Two grades of base material were used with thicknesses in the range of 0.8 - 2 mm. RSW joints were manufactured using an automated welding source, and their microstructural characteristics were evaluated by optical and electron microscopy to emphasise the importance of using optimal welding regimes to reduce weld failure. Mechanical properties were evaluated using Vickers microhardness measurements and nanoindentation. Tensile tests were carried out to assess the force-displacement curves and identify the failure mode. The results of the study show that RSW is a promising method for fabricating lightweight steel structural systems when the current, time, and interelectrode forces of RSW are carefully selected.